EDUKASI PENCEGAHAN PENYAKIT PARU PADA ANAK JALANAN DAN MARJINAL KOMUNITAS SAHABAT ANAK GROGOL JAKARTA BARAT - Octavia Dwi Wahyuni; Hadisono Hadisono; Twidy Tarcisia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Lung and respiratory disease are a condition that generates the largest burden of disability-adjusted life-years (DALYs) and most common in the world. The top estimated 10 causes of death worldwide are in 2040, three of them are due to lower respiratory tract infections, chronic obstructive pulmonary disease and lung cancer, which are members of